Case Study on Social Innovation in Four Cities in Colombia: Bogotá, Buenaventura, Cali and Cartagena (2016)
Introduction: This article shows a work performed in four cities in Colombia with one of the longest running awards in the Colombian social sphere: Fundación Corona’s Civic Award. Methodology: A mixed study with a descriptive approach was conducted resulting in six independent variables that explain the behavior of innovation: experience, number of members in the organization, community participation in the initiative, if the initiatives have been nominees for the award at other times, amount of funding used, and whether the initiative has legal status. Results: In relation to the qualitative phase, six significant elements were found in the mission of organizations related to social innovation projects: improved quality of life of participants and the community, peace-building, promotion of culture, opportunities for participation, use of leisure time, and strengthening of social fabric. Conclusions: This study case allows to identify, in the light of social innovation, the main features of grassroots organizations in the field of social action, in Bogotá, Buenaventura, Cali and Cartagena.